2009
DOI: 10.1128/aem.01046-08
|View full text |Cite
|
Sign up to set email alerts
|

Employment of a Promoter-Swapping Technique Shows that PhoU Modulates the Activity of the PstSCAB 2 ABC Transporter in Escherichia coli

Abstract: Expression of the Pho regulon in Escherichia coli is induced in response to low levels of environmental phosphate (P i ). Under these conditions, the high-affinity PstSCAB 2 protein (i.e., with two PstB proteins) is the primary P i transporter. Expression from the pstSCAB-phoU operon is regulated by the PhoB/PhoR twocomponent regulatory system. PhoU is a negative regulator of the Pho regulon; however, the mechanism by which PhoU accomplishes this is currently unknown. Genetic studies of phoU have proven to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 39 publications
3
82
0
5
Order By: Relevance
“…All previous studies that directly measured the rate of P i transport by PstSCAB in the presence and absence of PhoU detected little (ϳ20%) to no difference (8,9,20). However, those studies focused on cells grown under low-P i conditions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…All previous studies that directly measured the rate of P i transport by PstSCAB in the presence and absence of PhoU detected little (ϳ20%) to no difference (8,9,20). However, those studies focused on cells grown under low-P i conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Second, phoU mutants display poor growth, loss of viability, and genetic instability. This led to attempts at developing E. coli and C. crescentus strains to overcome these obstacles (8,20). However, those systems remained imperfect; the E. coli systems continued to display genetic instability in high-phosphate medium (20), while the C. crescentus system did not overcome the expression differences or the viability phenotype (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The speed at which this degradation initiated raised the possibility that a small molecule or mechanical signal may be the cellular indicator of carbon source availability.Glucose and phosphate transport into the cell is monitored by the proteins GlcIIa and PhoU, respectively (Deutscher et al 2006;Rice et al 2009), and the slowing of phosphate transport upon phosphate limitation signals production of a small RNA that stimulates rpoS translation (Ruiz and Silhavy 2003). To test whether metabolite transport alone could trigger RpoS degradation, the glucose analog a-methylglucoside was added to starved cells.…”
mentioning
confidence: 99%
“…One of the first proposals was that it could interact with the PhoU protein from the phosphate-transport (Pst) system; however, the experimental data are not sufficient to support this hypothesis. It has been observed that the Pst system plays a role in this regulation, with PhoU being a negative regulator of the Pho system (Rice et al, 2009).…”
Section: Introductionmentioning
confidence: 99%